Stress Management and Psychosocial Adaptation Education for Pregnant Women at Risk of Gestational Hypertension - Liliek Pratiwi (Universitas Malahayati Lampung, 2026)
ABSTRACT Gestational hypertension is a prevalent pregnancy complication significantly exacerbated by chronic, unmanaged stress and inadequate psychosocial adaptation. Despite its profound impact on maternal and fetal health, conventional antenatal care frequently overlooks the psychological needs of expectant mothers. This community service program aimed to address this critical gap by enhancing the psychological well-being and functional health literacy of pregnant women at a high risk of developing gestational hypertension. The educational intervention was conducted in Karangmulya Village, targeting a demographic of 30 high-risk expectant mothers. A health promotion approach was utilized, primarily employing a structured didactic lecture combined with an interactive discussion. The core curriculum focused on actionable, evidence-based stress management techniques and psychosocial adaptation strategies. To evaluate the program's overall effectiveness, pre-test and post-test assessments were administered to measure knowledge absorption. The results demonstrated a substantial improvement in the participants' understanding of stress triggers and adaptation mechanisms. Prior to the intervention, the average knowledge score was notably low at 42%, but it surged to 86% following the lecture, reflecting a significant 44% increase. In conclusion, equipping vulnerable pregnant women with practical stress management skills successfully improves their psychosocial resilience. Integrating such targeted, non-pharmacological educational interventions into routine maternal healthcare is essential to mitigate emotional distress and promote safer pregnancy outcomes. Keywords: Gestational Hypertension, Health Education, Maternal Health, Psychosocial Adaptation, Stress Management.